THE ROLE OF THE PIGF/SFLT-1 RELATIONSHIP IN PREDICTING PREECLAMPSIA (LITERATURE REVIEW) - Irina Venzkovskaya; Anastasiіa Padchenko (Ukrainian Scientific Medical Youth Journal, 2019)
Endothelial vascular dysfunction is an important link in the pathogenesis of preeclampsia – a pathological condition that occupies a leading position in the structure of maternal morbidity and mortality, perinatal mortality and intrauterine growth retardation. Assessment of the state of vascular endothelium during pregnancy is currently an informative method for predicting the development of this disease. The article summarizes the significance of the most studied specific biochemical markers of endothelial dysfunction, such as soluble fms-like tyrosine kinase-1 (sFlt-1) and placental growth factor (PlGF), in relation to the prognosis and diagnosis of preeclampsia. Since the etiopathogenesis of preeclampsia is caused by the development of endothelial insufficiency and impaired vascular formation in the mother-placenta-fetus system, the choice of angiogenesis biomarkers as screening tests is justified from a logical point of view. As a screening indicator of the risk of preeclampsia, the most reliable determination of the ratio sFlt-l/PIGF, which reflects the change in both biomarkers during preeclampsia, is more pronounced than a separate definition of any of these factors. In women with the pathological course of the gestational process, in several weeks before the onset of the first clinical symptoms, a decrease in PlGF concentration and a significant increase in sFlt-1 concentration are observed in 92.5% of cases, which makes it possible to determine the risk of gestosis long before the onset of its severe clinical manifestations and to develop an optimal management for patients with this pathology. This topic is relevant, since the prevalence of preeclampsia according to different authors varies from 3 to 8% among pregnant women in developed countries. In general, up to 10-15% of maternal deaths are associated with preeclampsia and eclampsia.